The Development of Chinese Vocabulary Listening Skills Among Grade 2 Students Through the Total Physical Response TPR Teaching Method: The Development of Chinese Vocabulary Listening Skills Among Grade 2 Students Through the Total Physical Response TPR Teaching Method - Surintaboon, Nanthatchaporn; Phorntaweekul, Satjatham (RATANABUTH JOURNAL, 2026)
The objectives of this research were: 1) to develop and determine the efficiency of Total Physical Response (TPR)-based learning activities at Anuban Tesaban Tambon Nadun School to meet the 80/80 efficiency criterion; 2) to compare students' Chinese vocabulary listening skills before and after implementing the TPR-based learning activities; and 3) to assess students' satisfaction with these activities. Utilizing a quasi-experimental, pretest-posttest design, the study was conducted with a purposive sample of 20 Grade 2 students at Anuban Tesaban Tambon Nadun School during the second semester of the 2025 academic year. The research instruments consisted of: 1) TPR-based lesson plans focusing on the topic “Occupations” 2) a 20-item Chinese vocabulary listening skill test with an overall reliability of .99; and 3) a 10-item satisfaction questionnaire regarding the learning activities. Data were analyzed using mean , standard deviation (S.D.), percentage, and the Wilcoxon Signed-Rank Test. The findings revealed that: 1. The efficiency (E1/E2) of the developed TPR-based learning activities for the Grade 2 students was 87.30/81.25, which successfully met the predefined 80/80 standard criterion. 2.The students taught through the TPR approach achieved a posttest mean score of 15.00, which was higher than their pretest mean score of 7.50. This improvement indicated that the posttest scores were significantly higher than the pretest scores at the .05 statistical level. 3.The students' overall satisfaction with the TPR-based learning activities was at a high level, with a mean score of 4.46.